Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Impacts of olfactory cues on equine feeding behavior - Erin B. Perry; Grace C. Handlos; Jesse M. Fenton (Journal of Equine Veterinary Science, 2024)

Coexistence between similar invaders: The case of two cosmopolitan exotic insects - Matthew B. Arnold; Michael Back; Michael Daniel Crowell; Nageen Farooq; Prashant Ghimire; Omon A. Obarein; Kyle E. Smart; Trixie Taucher; Erin VanderJeugdt; Kayla I. Perry; Douglas A. Landis; Christie A. Bahlai (Ecology, 2023)
Biological invasions are usually examined in the context of their impacts on native species. However, few studies have examined the dynamics between invaders when multiple exotic species successfully coexist in a novel environment. Yet, long‐term coexistence of now established exotic species has been observed in North American lady beetle communities. Exotic lady beetles Harmonia axyridis and Coccinella septempunctata were introduced for biological control in agricultural systems and have since become dominant species within these communities. In this study, we investigated coexistence via spatial and temporal niche partitioning among H. axyridis and C. septempunctata using a 31‐year data set from southwestern Michigan, USA. We found evidence of long‐term coexistence through a combination of small‐scale environmental, habitat, and seasonal mechanisms. Across years, H. axyridis and C. septempunctata experienced patterns of cyclical dominance likely related to yearly variation in temperature and precipitation. Within years, populations of C. septempunctata peaked early in the growing season at 550 degree days, while H. axyridis populations grew in the season until 1250 degree days and continued to have high activity after this point. C. septempunctata was generally most abundant in herbaceous crops, whereas H. axyridis did not display strong habitat preferences. These findings suggest that within this region H. axyridis has broader habitat and abiotic environmental preferences, whereas C. septempunctata thrives under more specific ecological conditions. These ecological differences have contributed to the continued coexistence of these two invaders. Understanding the mechanisms that allow for the coexistence of dominant exotic species contributes to native biodiversity conservation management of invaded ecosystems.

Advocating for Science: Amici Curiae Brief of Wetland and Water Scientists in Support of the Clean Water Rule - Royal C. Gardner; Erin Okuno; Steph Tai; M. Siobhan Fennessy; Carol A. Johnston; Marinus L. Otte; Margaret Palmer; James E. Perry; Charles Simenstad; Benjamin R. Tanner; Dan Tufford; R. Eugene Turner; et al. (Wetlands, 2019)

Warming and provenance limit tree recruitment across and beyond the elevation range of subalpine forest - Lara M. Kueppers; Erin Conlisk; Cristina Castanha; Andrew B. Moyes; Matthew J. Germino; Perry de Valpine; Margaret S. Torn; Jeffry B. Mitton (Global Change Biology, 2017)
Climate niche models project that subalpine forest ranges will extend upslope with climate warming. These projections assume that the climate suitable for adult trees will be adequate for forest regeneration, ignoring climate requirements for seedling recruitment, a potential demographic bottleneck. Moreover, local genetic adaptation is expected to facilitate range expansion, with tree populations at the upper forest edge providing the seed best adapted to the alpine. Here, we test these expectations using a novel combination of common gardens, seeded with two widely distributed subalpine conifers, and climate manipulations replicated at three elevations. Infrared heaters raised temperatures in heated plots, but raised temperatures more in the forest than at or above treeline because strong winds at high elevation reduced heating efficiency. Watering increased season‐average soil moisture similarly across sites. Contrary to expectations, warming reduced Engelmann spruce recruitment at and above treeline, as well as in the forest. Warming reduced limber pine first‐year recruitment in the forest, but had no net effect on fourth‐year recruitment at any site. Watering during the snow‐free season alleviated some negative effects of warming, indicating that warming exacerbated water limitations. Contrary to expectations of local adaptation, low‐elevation seeds of both species initially recruited more strongly than high‐elevation seeds across the elevation gradient, although the low‐provenance advantage diminished by the fourth year for Engelmann spruce, likely due to small sample sizes. High‐ and low‐elevation provenances responded similarly to warming across sites for Engelmann spruce, but differently for limber pine. In the context of increasing tree mortality, lower recruitment at all elevations with warming, combined with lower quality, high‐provenance seed being most available for colonizing the alpine, portends range contraction for Engelmann spruce. The lower sensitivity of limber pine to warming indicates a potential for this species to become more important in subalpine forest communities in the coming centuries.

Impulsivity (delay discounting) as a predictor of acquisition of IV cocaine self-administration in female rats - Jennifer L. Perry; Erin B. Larson; Jonathan P. German; Gregory J. Madden; Marilyn E. Carroll (Psychopharmacology, 2005)